The Role of Content and Language Integrated Learning (CLIL) in Teaching English for Tourism: Challenges and Implications for ESP Teachers - Diah Aju Hermawati (Journal of English in Academic and Professional Communication, 2022)
CLIL programs at the university level are usually associated with ESP courses, we analyze the case regards to the position of CLIL and ESP in Tourism study. As CLIL programs are promoted to improve students’ language proficiency in English, we explore the importance of language learning in these programs and the implications derived from ESP. Data were obtained from class observation and also lecturer and student views on CLIL expressed in focus groups and a questionnaire. Findings show imprecise guidelines for CLIL implementation. Although we can observe a well-organized shift from ESP to CLIL, lecturer and student perspectives provide useful insights for action that can be taken by ESP course designers to adapt courses to make them more relevant to students’ discipline-related needs. Deal with these findings, we propose engaging in collaboration with content lecturers to advance Tourism Department’s graduates’ proficiency in English.